2015
DOI: 10.1371/journal.pntd.0004264
|View full text |Cite
|
Sign up to set email alerts
|

A Library of Plasmodium vivax Recombinant Merozoite Proteins Reveals New Vaccine Candidates and Protein-Protein Interactions

Abstract: BackgroundA vaccine targeting Plasmodium vivax will be an essential component of any comprehensive malaria elimination program, but major gaps in our understanding of P. vivax biology, including the protein-protein interactions that mediate merozoite invasion of reticulocytes, hinder the search for candidate antigens. Only one ligand-receptor interaction has been identified, that between P. vivax Duffy Binding Protein (PvDBP) and the erythrocyte Duffy Antigen Receptor for Chemokines (DARC), and strain-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
74
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(85 citation statements)
references
References 107 publications
8
74
0
3
Order By: Relevance
“…Then such paralogs that underwent an adaptive divergence in the P. vivax lineage, have been under purifying selection in the extant P. vivax populations indicating functional constrains. Interestingly, there is evidence that two of those genes (PVX_082675 and PVX_82680) are immunogenic and the latter is recognized by semi-immune individuals without fever after being challenged with sporozoites indicating that those antibodies could be associated with protection (Arévalo-Herrera et al, 2016; Hostetler et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Then such paralogs that underwent an adaptive divergence in the P. vivax lineage, have been under purifying selection in the extant P. vivax populations indicating functional constrains. Interestingly, there is evidence that two of those genes (PVX_082675 and PVX_82680) are immunogenic and the latter is recognized by semi-immune individuals without fever after being challenged with sporozoites indicating that those antibodies could be associated with protection (Arévalo-Herrera et al, 2016; Hostetler et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Recent protein-protein interaction assays have shown that MSP7 proteins do not appear to bind to the same host receptor [26]; moreover, these proteins seem to be forming different protein complexes in the parasite [7, 2730], maybe to perform different parasite-host interactions. Such results flout the functional redundancy hypothesis [15, 18]; functional divergence in MSP7 paralogs thus appears to be probable.…”
Section: Introductionmentioning
confidence: 99%
“…! have improved success rates in the production of soluble protein for use in immunoepidemiology [43] and receptor-ligand interaction studies [22,44]. We chose to use transiently transfected, non-adherent HEK293E cells for protein expression; 15 of 22 proteins (68%) were expressed with detection by anti-pentahistidine antibody in our study.…”
Section: Discussionmentioning
confidence: 99%